Aplasia Cutis Congenita in the Setting of Maternal Cystic Fibrosis - Govind Kallumkal; Robert Egerman (Annals of Internal Medicine: Clinical Cases)
Aplasia cutis congenita is a rare scalp defect. An affected neonate was delivered after in utero exposure beginning in the midtrimester to elexacaftor/tezacaftor/ivacaftor for maternal cystic fibrosis management. Although aplasia cutis congenita has many potential etiologies, maternal cystic fibrosis transmembrane regulator modulator therapy has not been implicated.